2004
DOI: 10.1111/j.1348-0421.2004.tb03556.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Hepatitis C Virus Replicon by RNA Interference Directed against the NS3 and NS5B Regions of the Viral Genome

Abstract: RNA interference (RNAi) is a phenomenon in which small interfering RNA (siRNA), an RNA duplex 21 to 23 nucleotides (nt) long, or short hairpin RNA (shRNA) resembling siRNA, mediates degradation of the target RNA molecule in a sequence‐specific manner. RNAi is now expected to be a useful therapeutic strategy for hepatitis C virus (HCV) infection. In the present study we compared the efficacy of a number of shRNAs directed against different target regions of the HCV genome, such as 5′‐untranslated region (5′UTR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 53 publications
5
49
1
Order By: Relevance
“…This technology is potentially applicable to drug targeting for genes involved in the pathogenesis of human diseases. For example, siRNAs against Fas and TNFa have been reported to control fulminant hepatitis 23,24 and septic shock in mice, 25 respectively, while others have been reported to successfully inhibit replication of hepatitis B virus, 26,27 hepatitis C virus, 28,29 and human immunodeficiency virus type 1. 30,31 The application of an siRNA to cancer therapy appears to be more complicated, as recent molecular analyses have revealed that most oncogenes involved in carcinogenesis have no or only subtle sequence changes, such as point mutations and translocation.…”
Section: Effects Of E6 Sirna On the Growth Of Hpv18-related Cancer Cellsmentioning
confidence: 99%
“…This technology is potentially applicable to drug targeting for genes involved in the pathogenesis of human diseases. For example, siRNAs against Fas and TNFa have been reported to control fulminant hepatitis 23,24 and septic shock in mice, 25 respectively, while others have been reported to successfully inhibit replication of hepatitis B virus, 26,27 hepatitis C virus, 28,29 and human immunodeficiency virus type 1. 30,31 The application of an siRNA to cancer therapy appears to be more complicated, as recent molecular analyses have revealed that most oncogenes involved in carcinogenesis have no or only subtle sequence changes, such as point mutations and translocation.…”
Section: Effects Of E6 Sirna On the Growth Of Hpv18-related Cancer Cellsmentioning
confidence: 99%
“…Immunofluorescence staining was performed essentially as described previously (Takigawa et al, 2004). Cells seeded on glass coverslips in a 24-well plate at a density of 4610 4 cells per well were infected with HCV.…”
Section: Methodsmentioning
confidence: 99%
“…Huh-7.5 cells stably harbouring an HCV subgenomic RNA replicon were prepared by using pFK5B/2884Gly, as described previously (Hidajat et al, 2005;Lohmann et al, 2001;Taguchi et al, 2004;Takigawa et al, 2004).…”
Section: Methodsmentioning
confidence: 99%